(untitled) (Vietnam Journal of Community Medicine, 2026)
Abstract: Objectives: To describe clinical and paraclinical characteristics and analyze factors associated with treatment outcomes of catheter-associated urinary tract infection (CAUTI) at the National Hospital for Tropical Diseases. Methods: Cross-sectional study with both retrospective and prospective components on 104 adult inpatients diagnosed with CAUTI in the ICU and Emergency departments, January 2022 - August 2024. Results: Mean age 63±17 years, 61.5% male, 52.9% aged over 65. Fever was the predominant symptom (94.2%). CRP was elevated in 97.9%, procalcitonin in 85.7%, and hypoalbuminemia in 91.2%. Fungi and bacteria were isolated equally (50% each). Candida tropicalis was most prevalent (25.4%), followed by C. albicans (17.5%); P. aeruginosa (13.5%) and E. coli (8.7%) were the leading bacterial pathogens. K. pneumoniae showed pan-carbapenem resistance. Factors associated with poor outcomes were: diabetes mellitus (OR=4.8; p=0.028), urolithiasis (OR=6.8; p=0.009), procalcitonin >1 ng/mL (OR=4.38; p=0.036) and WBC >15 G/L (OR=4.62; p=0.032). Conclusions: CAUTI in a tertiary infectious-disease hospital is characterized by high fungal burden and significant antimicrobial resistance. Diabetes, urolithiasis, elevated procalcitonin and leukocytosis are key prognostic factors that warrant close monitoring.